Does Standing Protect Bone Density in Patients With Chronic Spinal Cord Injury - Goktepe, Ahmet Salim (American Paraplegia Society, 2008)
BACKGROUND/OBJECTIVE: To compare the t-scores of proximal femur and lumbar spine of patients with spinal cord injury (SCI) with different levels of weight bearing. METHODS: Cross-sectional study comparing 3 groups of patients with SCI: patients with daily standing times of more than 1 hour, patients with daily standing times of less than 1 hour, and nonstanding patients. Seventy-one patients with chronic SCI were recruited. They were assigned to 1 of 3 groups according to their reported daily standing time. The bone density of lumbar and proximal femoral regions was measured with dual-energy x-ray absorptiometry. RESULTS: The 3 groups were similar in terms of demographics and clinical variables. No significant difference was found among the mean t-scores of lumbar and proximal femoral regions of the groups. However, the patients in the group that stood more than 1 hour daily had a slight tendency to have higher t-scores than those in the control group. CONCLUSIONS: There was no significant difference among the 3 groups. However, standing might be partially helpful in protecting the bone density in SCI by opposing the effects of immobilization.